Effects of nitrogen film cooling on ignition transition of gaseous oxygen/kerosene spray combustor. Issue 7 (19th May 2023) - Song, Wooseok; Shin, Dongsoo; Son, Min; Koo, Jaye
ABSTRACT: The effects of nitrogen film cooling on ignition transition under different conditions of film cooling injection pressure were observed. Gaseous oxygen and liquid kerosene were used as propellants, injected using a shear coaxial injector. Gaseous nitrogen as the film coolant was injected along the gap between the combustion chamber and outer injector walls. A dynamic pressure transducer and a high-speed camera with a band-pass filter were respectively used. The over-peak pressure and pressure rise time were detected in cases with film cooling. With the increase in the differential pressure, the over-peak pressure decreased, and pressure rise time increased. These phenomena are explained by the interruption of normal propellant injection in the mixing zone of propellant. The combustion instability intensity decreased with the increase in the differential pressure between the combustion chamber and injected film coolant. Flame structures were visualized to confirm the unstable combustion flame during the ignition transition.